2020
DOI: 10.5194/tc-2019-334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ISMIP6 projections of ocean-forced Antarctic Ice Sheet evolution using the Community Ice Sheet Model

Abstract: Abstract. The future retreat rate for marine-based regions of the Antarctic Ice Sheet is one of the largest uncertainties in sea-level projections. The Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6) aims to improve projections and quantify uncertainties by running an ensemble of ice sheet models with atmosphere and ocean forcing derived from global climate models. Here, ISMIP6 projections of ocean-forced Antarctic Ice Sheet evolution are illustrated using the Community Ice Sheet Model (CISM). Using… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…For both the MISMIP3d and the sub-ice-shelf melt experiments, and for any choice of p or grid resolution, the results with the DIVA solver are close to those with the more expensive BP solver, consistent with CISM simulations of Greenland and Antarctica (Lipscomb et al, 2019(Lipscomb et al, , 2020. The SSA solver, which is valid when basal stresses are low enough that there is little vertical shear, gives results similar to DIVA and BP in the MISMIP+ framework, but overestimates the ice viscosity for MISMIP3d, leading to greater grounding-line advance.…”
Section: Experiments 2: High Basal Melt Ratesupporting
confidence: 60%
See 2 more Smart Citations
“…For both the MISMIP3d and the sub-ice-shelf melt experiments, and for any choice of p or grid resolution, the results with the DIVA solver are close to those with the more expensive BP solver, consistent with CISM simulations of Greenland and Antarctica (Lipscomb et al, 2019(Lipscomb et al, , 2020. The SSA solver, which is valid when basal stresses are low enough that there is little vertical shear, gives results similar to DIVA and BP in the MISMIP+ framework, but overestimates the ice viscosity for MISMIP3d, leading to greater grounding-line advance.…”
Section: Experiments 2: High Basal Melt Ratesupporting
confidence: 60%
“…In regions where the seabed deepens upstream of the grounding line, this retreat can be self-reinforcing (Schoof, 2007a). Research is ongoing (Seroussi et al, 2020;Rückamp et al, 2020;Lipscomb et al, 2020) to better understand and model the physical processes responsible for marine ice-sheet behavior, in order to better forecast future mass loss and sea-level rise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscosity is vertically averaged, and basal friction is cast in terms of the depth-averaged velocity. This solver has been used by continental-scale models to investigate dynamics and interactions with climate for the Greenland and Antarctic ice sheets (Arthern et al, 2015;Arthern and Williams, 2017;Lipscomb et al, 2019Lipscomb et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…In their extended ISMIP6 study, Lipscomb et al (2021) found two parameters to be especially important to the sensitivity of the ice sheet. The first, γ 0 , is a constant in the TF parameterization that scales melt rates for a given ocean TF.…”
Section: Introductionmentioning
confidence: 99%